Pengaruh Tingkat Kepercayaan,Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan JNE Klaten - Maharani Dewi Nilamsari; Edi Purwanto; Ngaisah (STIE Wijaya Mulya, 2024)
The aim of this research is to determine the influence of the level of trust, service quality and price on JNE Klaten customer satisfaction. In this study, the data and summary data used are primary data. Data collection using a questionnaire is a data collection method that involves analyzing basic overview questions by utilizing a closed interview strategy with JNE users in Klaten. The processing and presentation of data in this research is by utilizing the SPSS application. The results of this research show that based on the test results it is known that the consumer trust level variable (X1) has a partial effect on JNE Klaten customer satisfaction, so the hypothesis is accepted. Based on the test results, it is known that the service quality variable (X2) has a partial effect on JNE Klaten customer satisfaction, so the hypothesis is accepted. Based on the results of the t test, it is known that the price variable has a significant value of 0.395 which is greater than 0.05, so the hypothesis is not accepted, which means that price has no partial effect on JNE Klaten customer satisfaction. Based on the results of the simultaneous f test, the calculated F value is greater than the F table (29.870 > 2.72), so the second hypothesis is accepted. Based on the results of multiple linear regression, the value b2 (0.463) > b1 (0.258) & b3 (0.078) is obtained, so hypothesis 3 is proven.